Proceedings of the 2010 Conference of the Center for Advanced Studies on Collaborative Research - CASCON '10 2010
DOI: 10.1145/1923947.1923951
|View full text |Cite
|
Sign up to set email alerts
|

Improving program navigation with an active help system

Abstract: When performing software change tasks, software developers spend a substantial amount of their time navigating dependencies in the code. Despite the availability of numerous tools to aid such navigation, there is evidence to suggest that developers are not using these tools. In this paper, we introduce an active help system, called Spyglass, that suggests tools to aid program navigation as a developer works. We report on the results of a laboratory study that investigated two questions: will developers act upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…We are aware of three fully implemented ICRSs that have been developed in the past. Spyglass [15] observes and analyzes user behavior to check whether certain steps could be replaced by IDE commands. The input data is the IDE command execution history.…”
Section: A Ide Command Recommender Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…We are aware of three fully implemented ICRSs that have been developed in the past. Spyglass [15] observes and analyzes user behavior to check whether certain steps could be replaced by IDE commands. The input data is the IDE command execution history.…”
Section: A Ide Command Recommender Systemsmentioning
confidence: 99%
“…Regarding the ICRSs utility, Spyglass evaluation showed that an ICRS can make developers aware of available tools to a similar degree to a tutorial, but with less effort [15]. Murphy-Hill et al showed that it is feasible to automatically recommend useful IDE commands to software developers [9].…”
Section: A Ide Command Recommender Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most domains, such as that of text collections or electronic retail, there are sets of frequently co-occurring items [3,19,46,52]. This phenomenon is even more noticeable in the domain of IDE commands, where certain sets of commands have to be used to complete specific tasks [46,56].…”
Section: Codismentioning
confidence: 99%
“…For example, Sage pops up a tip teaching the user about the Toggle-Comment feature (hotkey: Ctrl+/), if it detects that a programmer is manually commenting several lines of code. Sage focuses on hotkey usage; Spyglass also monitors an IDE user, but focuses on code navigation tasks [33]. Sage also records the number of times a user could have used a feature but did not.…”
Section: Illustrative Examplementioning
confidence: 99%